Les forêts de la Tshopo : écologie, histoire et composition - De Cannière, Charles; Ponette, Quentin; Defourny, Pierre; Bogaert, Jan; Beeckman, Hans (Uliège Library, 2020)
The forests of the Congo Basin are the second largest tropical forest in the world. For a long time, conflicts of use have been numerous. In order to preserve its ecosystem services, the exploitation of these forests should integrate the principles of sustainable management. Information, education, training and outreach work is therefore necessary within Congolese society. University cooperation is an appropriate way to meet this need for training for all actors concerned with the resources present in the forests of Tshopo (former Province Orientale). A targeted inter-university project financed by ARES (formerly CUD) entitled "Support for the organization of a master's degree in forest management to strengthen the capacities of Congolese researchers with a view to the socio-economic recovery of the Democratic Republic of Congo - AFORCO" provided for two main activities: postgraduate training and the production of doctoral theses in disciplines relevant to forest management. The capacities of 16 experts were strengthened through a DES in sustainable forest management at the University of Kisangani (2009-2011); in December 2015, two PhD theses were presented and defended at Gembloux Agro-Bio Tech in the fields of wood biology and landscape ecology. This book provides a review of the studies carried out thanks to the AFORCO project and related projects, mainly in the form of final works and PhD theses on the forest ecosystems of the Tshopo. This book is primarily intended for researchers concerned with the challenges of sustainable development in developing countries characterized by the presence of still abundant natural resources. The studies presented highlight the added value of academic cooperation, the need for long-term scientific collaborations and the potential synergies of North-South academic exchanges. / Les forêts du bassin du Congo constituent le deuxième plus grand massif de forêts tropicales au monde. Depuis longtemps, les conflits d'usages y ont été nombreux. Afin de préserver ses services écosystémiques, l'exploitation de ces forêts devrait intégrer les principes de l'aménagement durable. Un travail d'information, d'éducation, de formation et de vulgarisation s'impose donc au sein de la société congolaise. La coopération universitaire constitue un moyen approprié de répondre à ce besoin de formations au profit de tous les acteurs concernés par les ressources présentes au sein des forêts de la Tshopo (ex Province orientale). Un projet interuniversitaire ciblé financé par l'ARES (ex CUD) intitulé « Appui à l'organisation d'un master en Aménagement forestier pour le renforcement des capacités des chercheurs congolais en vue de la relance socio-économique de la République démocratique du Congo - AFORCO » prévoyait deux activités principales : une formation de troisième cycle et la réalisation de thèses de doctorat dans des disciplines pertinentes pour l'aménagement forestier. Les capacités de 16 experts ont été renforcées à travers un DES en aménagement forestier durable à l'université de Kisangani (2009-2011) ; en décembre 2015, deux thèses de doctorat ont été présentées et défendues à Gembloux Agro-Bio Tech dans les domaines de la biologie du bois et de l'écologie du paysage. Cet ouvrage donne une revue des études concrétisées grâce au projet AFORCO et des projets apparentés, principalement sous forme de travaux de fin d'études et de thèses de doctorat portant sur les écosystèmes forestiers de la Tshopo. Ce livre s'adresse d'abord aux chercheurs préoccupés par les défis du développement durable dans des pays en voie de développement caractérisés par la présence de ressources naturelles encore abondantes. Les études présentées mettent en évidence la valeur ajoutée de la coopération universitaire, la nécessité de collaborations scientifiques de longue durée et les synergies potentielles d'échanges académiques Nord-Sud.